2006
DOI: 10.5380/pes.v16i0.7479
|View full text |Cite
|
Sign up to set email alerts
|

AVALIAÇÃO DA CONCENTRAÇÃO DE METAIS PESADOS EM TECIDO DE OSTRAS <i>Crassostrea gigas</i> (MOLUSCA, BIVALVE) CULTIVADAS NA BAÍA DA BABITONGA, LITORAL NORTE DE SANTA CATARINA

Abstract: Este trabalho objetivou avaliar a concentração de metais pesados em tecidos de ostras Crassostrea gigas cultivadas em 4 pontos da Baía da Babitonga, litoral Norte do Estado de Santa Catarina. Para tanto, foram instaladas estruturas de cultivo em cada ponto no sistema longline. Durante um ano foram medidos os parâmetros físico-químicos da água, quinzenalmente, e realizadas análises químicas bimensais dos metais pesados arsênio, cádmio, cobre, níquel e zinco no sedimento, na água e no tecido de ostras. Os result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
3
0
6
Order By: Relevance
“…At Babitonga Bay, previous studies have found disturbing levels of contaminants in fishery resources (Cremer et al 2006;Tureck et al 2006). Resident populations of the Franciscana dolphin (Pontoporia blainvillei), which is at a high trophic level, showed high levels for octocrylene (Gago-Ferrero et al 2013) and PCBs (Dorneles et al 2013) in this area.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…At Babitonga Bay, previous studies have found disturbing levels of contaminants in fishery resources (Cremer et al 2006;Tureck et al 2006). Resident populations of the Franciscana dolphin (Pontoporia blainvillei), which is at a high trophic level, showed high levels for octocrylene (Gago-Ferrero et al 2013) and PCBs (Dorneles et al 2013) in this area.…”
Section: Discussionmentioning
confidence: 71%
“…Our results show that fishers are at risk of contamination due to the consumption of several species. For example, among the species most consumed are oysters (Crassostrea brasiliana / C. rhizophorae), which had a cadmium level of 3.08 ppm (Tureck et al 2006). This is above the maximum limit (0.05 mg.kg-1) established by the MERCOSUL Technical Regulation (ANVISA 2013) for raw, frozen, or chilled fish, except for bonito, carapeba, eel, mullet, mackerel, sardines, tuna and flatfish (0.10 mg.kg-1), bluerunner and swordfish (0.30 mg.kg-1), cephalopod and bivalve mollusks (2.00 mg.kg-1), and crustaceans (0.50 mg.kg-1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo Tureck et al (2004) MONTANHINI NETO, R. e OSTRENSKY, A. Revisão: Uso de modelos matemáticos para avaliação da influência de variáveis ambientais sobre o desenvolvimento de ostras no Brasil. PUBVET, Londrina, V. 6, N. 4, Ed.…”
Section: Efeito Das Variáveis Ambientais No Crescimento De Ostrasunclassified
“…Entre as atividades econômicas sustentadas por este sistema costeiro, destacam-se as atividades portuárias, a pesca e o cultivo de organismos marinhos, principalmente a ostreicultura (Tureck et al 2004). Esta última atualmente possui quatro áreas delimitadas pelo Ministério do Meio Ambiente para esta finalidade.…”
Section: áRea De Pesquisaunclassified